PENGARUH STRES KERJA DAN WORK-FAMILY CONFLICT TERHADAP KINERJA YANG DIMODERASI STRATEGI COPING (Studi Pada Tenaga Kesehatan Rsu Kertha Usada Di Kabupaten Buleleng) - Luh Budi Yani; Nasharuddin Mas; Muchlis Mas’ud (Juremi: Jurnal Riset Ekonomi, 2026)
The expected objective in this study is to analyze the effect of work stress and work-family conflict on performance moderated by coping strategies.This study uses a quantitative research approach with the type of research being explanatory research. The population in this study were all Medical Personnel of Kertha Usada Hospital in Buleleng Regency totaling 387 people. To measure the sample size to be studied, the researcher used the Slovin formula, which amounted to 80 people. The sampling technique used was probability sampling with the technique taken, namely proportionate stratified random sampling. The data analysis technique used in this study was Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS software version 4.The results showed that work stress was able to reduce performance. Work-family conflict was able to reduce performance. Coping strategies were not able to improve performance. Work stress was not able to reduce performance that was potentially moderated by coping strategies. Work-family conflict was able to reduce performance that was purely moderated by coping strategies.